Implementasi “Aku Sayang Lingkungan” Anak-Anak Usia Dini pada kegiatan Sanitary Camp di PAUD Ummi Rodiah di Kampung Pangan Inovatif, Palembang - Najmah, Najmah; Azizah, Shinta; Iqlima, Erni; Rachmawati, Aisyah; Putrisha, Shantya Adeline; Khoirunnisa, Salsabila; Hanifah, Arindi Dinda; Elwin, Ghani El Mughni Muhammad Hidayatullah; Utama, Feranita; Idris, Haerawati; Arinda, Ditia Fitri; Trisnaini, Inoy; Misnaniarti, Misnaniarti; Indahsari, Siti Rahmi; Suhendra, Ahmad Adi; Mufarika, Rully (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2023)
Humans and the environment have a mutually correlated and inseparable relationship, the behavior of pollution and environmental destruction by humans will cause the environment to become damaged and polluted and will ultimately have bad consequences for humans themselves. This shows that changing human behavior towards the environment is the only way to improve the environment. Concern and love for the environment should be instilled in children from an early age because children and children are autonomous subjects who have seeds of character from the very beginning of their lives. The purpose of this service is environmental education for children, so that children are aware and willing to be responsible for protecting the environment and form attitudes towards environmental preservation and the ability to solve environmental problems. The service method used in this activity is by delivering interactive learning material by holding meetings directly with the children at Ummi Rodiah's Early Childhood Education, Plaju. Respondents in this study were early childhood children from Ummi Rodiah's Paud, Plaju and elementary school children around Ummi Rodiah's Paud, totaling 52 people. The concept applied to this activity is learning while playing with educational efforts regarding Clean and Healthy Behavior (PHBS), filling my plate, how to maintain cleanliness and environmental health, sorting waste, to getting to know and planting Family Medicinal Plants (TOGA). The results of this service involve teachers, lecturers and students of the Faculty of Public Health, University of Sriwijaya as volunteers. children are able to recognize the environment and indirectly provide education to children about the importance of keeping the environment clean can make children act and behave in love for the environment by keeping the environment clean. With the holding of this community service activity, it is hoped that a serious response from all parties is needed to care about preventing more serious environmental damage for the survival of all mankind.